Cardiac Implantable Electronic Device Removal in Patients with Left Ventricular Assist Device Associated Infections. (8th July 2014) - KRISHNAMOORTHY, ARUN; POKORNEY, SEAN D.; LEWIS, ROBERT K.; DAUBERT, JAMES P.; GREENFIELD, RUTH A.; HEGLAND, DONALD D.; MILANO, CARMELO A.; ROGERS, JOSEPH G.; SCHRODER, JACOB N.; PATEL, CHETAN B.; PICCINI, JONATHAN P.
CIED Removal in LVAD Infections Introduction Heart failure patients with left ventricular assist devices (LVADs) are at risk for infection. Cardiac implantable electronic devices (CIEDs) are commonly present in these patients. The course of infections in patients with an LVAD and a CIED is not well described. Methods and Results We identified 6 patients with a durable LVAD that underwent CIED removal because of an LVAD associated infection (LVADI). Patient and infection characteristics, management strategy, and clinical outcomes are described. All 6 patients were male, and the mean age was 59.6 years (range 43–72). Four of 6 patients had an ischemic cardiomyopathy, and 3 patients were diabetic. The median creatinine clearance for patients was 40.5 mg/dL (range 19–65). Five of 6 patients had a continuous flow LVAD placed as destination therapy. Four of 6 patients had a previous LVADI managed medically before the current infection leading to CIED removal. The indication for CIED removal was a bloodstream infection in 5 of 6 patients. Three of these patients had potential vegetations identified by echocardiography on device leads. The mean implanted age of the removed leads was 62 months (range 1–179), and 1 of the 6 patients experienced a procedural complication (hematoma) from CIED removal. Four of 6 patients that underwent CIED removal for an LVADI had recurrence of infection. Five of 6 patients died during the initial presentation or from repeat presentation for infection. Conclusion Despite CIED removal for an LVADI, recurrent infections are common and mortality remains high.